Advances in Computational Intelligence Systems Contributions Presented at the 16th UK Workshop on Computational Intelligence, September 7-9, 2016, Lancaster, UK - Angelov, Plamen; Gegov, Alexander; Jayne, Chrisina; Shen, Qiang; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The book is a timely report on advanced methods and applications of computational intelligence systems. It covers a long list of interconnected research areas, such as fuzzy systems, neural networks, evolutionary computation, evolving systems and machine learning. The individual chapters are based on peer-reviewed contributions presented at the 16th Annual UK Workshop on Computational Intelligence, held on September 7-9, 2016, in Lancaster, UK. The book puts a special emphasis on novels methods and reports on their use in a wide range of applications areas, thus providing both academics and professionals with a comprehensive and timely overview of new trends in computational intelligence.
Search and Optimisation (SO) -- Modelling and Simulation (MS) -- Analysis and Detection (AD) -- Cognition and Control (CC) -- Learning and Evolution (LE) -- Clustering and Regression (CR).
Keywords: Computational intelligence; Computer vision; Control engineering; Artificial intelligence; Computational Intelligence; Computer Vision; Control and Systems Theory; Artificial Intelligence